Saudi Students’ Translation Strategies in an Undergraduate Translator Training Program - Atari, Omar (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis paper reports on the findings of an empirical study conducted on the strategies employed by a sample of undergraduate Saudi translator trainees while translating. The study uses the think-aloud protocol (i.e. the subjects’ verbal reports of what’s going on in their heads while translating) as a technique for soliciting the data. The researcher has found that the strategies of ST and TT monitoring at the word or sentence level are employed most frequently (i.e. language-based strategies). Other important strategies, namely text contextualization and inferencing and reasoning are the least frequently used (i.e. knowledge-based strategies). Hence, the need for training translator trainees in the use of these strategies as well as the recognition and utilization of larger textual elements.